High Fat Diet Dysbiotic Mechanism of Decreased Gingival Blood Flow - Stanisic, Dragana; Jeremic, Nevena; Majumder, Suravi; Pushpakumar, Sathnur; George, Akash; Singh, Mahavir; Tyagi, Suresh C. (Frontiers in Physiology, 2021)
The gut microbiome plays anhasve very important role in human health and its influences on the development of various numerous diseasesdiseases is well known. In this study we investigated the effect of high fat diet (HFD) on the onset of dysbiosis, gingival blood flow decreasedecreases and the periodontal matrix remodeling. We established a dysbiosis model (HFD group) and probiotic model by Lactobacillus Rhamnosus GG (LGG) treatment for 12 weeks. Fecal samples were collected 24 hours before mice sacrificing, while Short Chain Fatty Acids (SCFA) analysis, DNA extraction and sequencing for metagenomic analysis were performed afterwards. After sacrificing the animalsanimals, we collected periodontal tissues and conducted comprehensive morphological and genetic analyses. While HFD reduced Bacteroidetes, SCFA and gingival blood flow, this type of diet increased Firmicutes, LPS binding protein, TLR4, pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), matrix metalloproteinases (MMP-2 and MMP-9) expression, and also altered markers of bone resorption (OPG and RANKL). However, LGG treatment mitigated these effects. Thus, it was observed that HFD increased molecular remodeling via inflammation, matrix degradation and functional remodeling and consequently cause reduced gingival blood flow. All of these changes may lead to the alveolar bone loss and the development of periodontal disease.